Actively controlled release of Dexamethasone from neural microelectrodes in a chronic in vivo study. (June 2017) - Boehler, C.; Kleber, C.; Martini, N.; Xie, Y.; Dryg, I.; Stieglitz, T.; Hofmann, U.G.; Asplund, M.
Abstract: Stable interconnection to neurons in vivo over long time-periods is critical for the success of future advanced neuroelectronic applications. The inevitable foreign body reaction towards implanted materials challenges the stability and an active intervention strategy would be desirable to treat inflammation locally. Here, we investigate whether controlled release of the anti-inflammatory drug Dexamethasone from flexible neural microelectrodes in the rat hippocampus has an impact on probe-tissue integration over 12 weeks of implantation. The drug was stored in a conducting polymer coating (PEDOT/Dex), selectively deposited on the electrode sites of neural probes, and released on weekly basis by applying a cyclic voltammetry signal in three electrode configuration in fully awake animals. Dex-functionalized probes provided stable recordings and impedance characteristics over the entire chronic study. Histological evaluation after 12 weeks of implantation revealed an overall low degree of inflammation around all flexible probes whereas electrodes exposed to active drug release protocols did have neurons closer to the electrode sites compared to controls. The combination of flexible probe technology with anti-inflammatory coatings accordingly offers a promising approach for enabling long-term stable neural interfaces.